A THE ORETICAL FRAMEWORK REGARDING THE CAUSES OF PEER BULLYING - Rizvance Masan, Sehida (International Scientific Journal Vision, 2020)
Peer bullying is a form of aggressive behavior with one or more students intentionally perpetuating against another, dominated by the imbalance power. Peer bullying has many negative effects on bullying children and adolescents as well as victims of such behavior. In this article, the definition of peer bullying and the different theoretical views about the causes of bullying are discussed. These different approaches are briefly summarized below. Although bullying has not been emhasized direclty in some theories, it has been found appropriate to address these theoretical views because they deal with aggression and it is accepted that bullying is a form of aggression.